mplementation of a functional prototype of a biometric system for the control of advisory services for integrative projects - Delgado Córdoba, Elkin Alcibíades; Andrea Castañeda, Paula; Parra Bohórquez, Yeimmi; Henao Villa, Cesar Felipe; García Arango, David Alberto; Delgado Córdoba, Elkin Alcibíades; Andrea Castañeda, Paula; Parra Bohórquez, Yeimmi; Henao Villa, Cesar Felipe; García Arango, David Alberto; Delgado Córdoba, Elkin Alcibíades; Andrea Castañeda, Paula; et al. (Corporación universitaria Americana, 2021)
In the present applied research, the attendance taking wasdigitized, improving the effectiveness and efficiency of saidtaking, through the use of biometric devices connected toa database supported on a platform specifically designedfor said task, providing an adequate control tool andconsultation, both for teachers, students and other members of the competent academic body to access the information that is stored automatically and in real time, when reporting attendance in the fingerprint reader located in the place of counseling defined by the staff in charge. This project improved the quality of the data collection process of assistance to theconsultancies of the integrative projects by the teacher to the students, who should occupy an assigned place according to the corresponding days and hours. With the present applied research, it was possible to facilitate registration through fingerprint readers, implemented and supported on innovative technology, properly programmed for this purpose, providing a higher level of confidence in terms of the veracity of the information entered and at the time of registration. consultation, since it is very difficult to falsify a fingerprint, this would give a greater degree of confidence in the information.